Miniaturized ultra-wideband coplanarwaveguide lowpass filter with extended stop band - Elmahjouby Sghir; Ahmed Errkik; Jamal Zbitou; Otman Oulhaj; Ahmed Lakhssassi; Mohamed Latrach (Institute of Advanced Engineering and Science, 2020)
In this article, we propose a novel design of large rejected band of miniaturized ultra wide band (UWB) of a planar CPW low pass filter “LPF” based on the use of periodic elements of ‘e’ slots. The goal of this work is to develop a new structure of Low Pass Filter with the following criterion: Miniature, Compact and Easy for Fabrication. The Miniaturization of this structure is achieved by entering the 'e' slot in etching area in the ground of CPW line, to save the standard gap of the adapted coplanar line. The designed coplanar LPF is a compact filter having a large band pass and extended stop band, with the possibility to associate easily with others RF and microwave planar circuits. The entire area of the proposed structure of CPW LPF is 14.3x20 mm2.